2020
DOI: 10.3389/fpls.2020.01200
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Root Transcriptional Responses to Low pH, Aluminum Toxicity and Iron Excess Under Pi-Limiting Conditions in Arabidopsis Wild-Type and stop1 Seedlings

Abstract: Acidic soils constrain plant growth and development in natural and agricultural ecosystems because of the combination of multiple stress factors including high levels of Fe 3+ , toxic levels of Al 3+ , low phosphate (Pi) availability and proton rhizotoxicity. The transcription factor SENSITIVE TO PROTON RHIZOTOXICITY (STOP1) has been reported to underlie root adaptation to low pH, Al 3+ toxicity and low Pi availability by activating the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…These genes include multiple upregulated genes in response to Ti encoding S, Boron (B), putative Silicon (Si) and amino acid transporters, that could play a role in enhancing nutrient uptake in response to Ti treatment ( Figure 5 ). We found that 31 of the so-called Pi-starvation responsive (PSR) genes ( Ojeda-Rivera et al., 2020 ) were upregulated DEGs in roots after 10 days of Ti treatment ( Supplementary Figure S5 ). PSR genes activated by Ti treatment included those encoding the purple acid phosphatases PAP1, and PAP2, which facilitate Pi uptake from organic molecules present in soil ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…These genes include multiple upregulated genes in response to Ti encoding S, Boron (B), putative Silicon (Si) and amino acid transporters, that could play a role in enhancing nutrient uptake in response to Ti treatment ( Figure 5 ). We found that 31 of the so-called Pi-starvation responsive (PSR) genes ( Ojeda-Rivera et al., 2020 ) were upregulated DEGs in roots after 10 days of Ti treatment ( Supplementary Figure S5 ). PSR genes activated by Ti treatment included those encoding the purple acid phosphatases PAP1, and PAP2, which facilitate Pi uptake from organic molecules present in soil ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Because in our experiments we used seedlings subjected to relatively short Al exposure times, the seedlings were very similar in size, thus normalization by plant gives a better outlook of the potential to exudate OAs under a specific type of stress. It was recently reported that low pH, which in turn interacts with other related stresses like P deficiency and Al and Fe toxicity in acid soils, contributes to STOP1 stabilization and ALMT1 transcriptional activation (Balzergue et al , 2017; Godon et al , 2019; Ojeda‐Rivera et al , 2020). Instead, the role of ALMT1 in roots of WT plants under P deficiency may be restricted to increase malate excretion to the root tip as a component of the meristematic exhaustion mechanism that triggers the root architecture modifications that characterize this nutritional stress (Gutiérrez‐Alanís et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of GO enrichment and cluster analysis by biological process were performed using g:profiler ( 71 ). Heatmaps of differentially expressed genes were constructed following published bioinformatics methods ( 72 ).…”
Section: Methodsmentioning
confidence: 99%